2015
DOI: 10.1016/j.chom.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Poxvirus Decapping Enzymes Enhance Virulence by Preventing the Accumulation of dsRNA and the Induction of Innate Antiviral Responses

Abstract: SUMMARY Poxvirus replication involves synthesis of double stranded RNA (dsRNA), which can trigger antiviral responses by inducing phosphorylation-mediated activation of protein kinase R (PKR) and stimulating 2’5’-oligoadenylate synthetase (OAS). PKR inactivates the translation initiation factor eIF2α via phosphorylation, while OAS induces the endonuclease RNase L to degrade RNA. We show that poxvirus decapping enzymes D9 and D10, which remove caps from mRNAs, inhibit these antiviral responses by preventing dsR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
135
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(136 citation statements)
references
References 58 publications
1
135
0
Order By: Relevance
“…The virally encoded decapping enzymes are usually expressed during early and late stages of viral infection to target host mRNAs such that host translation machinery is available almost exclusively for translation of viral RNAs (Liu et al, 2015). However, none of the MdSGHV genes had any significant homologies to known viral decapping enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The virally encoded decapping enzymes are usually expressed during early and late stages of viral infection to target host mRNAs such that host translation machinery is available almost exclusively for translation of viral RNAs (Liu et al, 2015). However, none of the MdSGHV genes had any significant homologies to known viral decapping enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, two very recent reports demonstrated that inhibiting the degradation of dsRNA by engineered mutations in VACV decapping genes and reducing expression of the exoribonuclease Xrn1 resulted in accumulation of dsRNA, activation of the PKR and OAS/RNase L pathways, and reduction of viral replication and virulence (47,48). Together with our results, these studies suggest that the rate of production and destruction of RNAs might be finely tuned to enable sufficient viral gene expression to support replication but not so much as to activate host antiviral dsRNA sensors.…”
Section: Discussionmentioning
confidence: 99%
“…Besides M156 and M029, ancillary MYXV factors may also control eIF2α phosphorylation. In addition to E3 and K3, VACV mRNA decapping enzymes (D9, D10) accelerate mRNA decay, thus limiting dsRNA accumulation, PKR activation, and contributing to virulence in vivo (13,14). Although MYXV encodes D9 and D10 orthologs (15), their contribution to regulating PKR and eIF2α phosphorylation remains unexplored.…”
mentioning
confidence: 99%